Comparison of the effect of a Physical Education-Based Stretching Program applied during the Warm-Up, ColdDown and both periods on hamstring extensibility in Primary Schoolchildren. - Romero-Ramos, Óscar; Mayorga-Vega, Daniel; Fernández-Rodríguez, Emilio; Merino-Marban, Rafael (My University, 2018)
Purpose. To compare the effects of a physical education-based stretching program applied during the warm-up, cold-down and both periods on hamstring extensibility in primary schoolchildren. Methods. A sample of 237 schoolchildren aged 7-12 years old (128 girls and 109 boys) from two primary school centres participated in the present study and met satisfactorily the inclusion and exclusion criteria. A cluster randomized controlled trial design was used. The classes balanced by grade were randomly assigned to the warm-up (n = 57), cold-down (n = 55), both periods (n = 61) or control groups (n = 64). During the physical education sessions, the students from the interventional groups performed a four-minute stretching program twice a week for eight weeks. The intervention program was applied during the warm-up (4 minutes), cold-down (4 minutes) and warm-up (2 minutes)-cold-down (2 minutes) for the warm-up, cold-down and both periods groups, respectively. Hamstring extensibility (estimated by the back-saver sit-and-reach test) was assessed at the beginning and at the end of the intervention program. Results. The one-way ANOVA (p < 0.001) on the average obtained in the back-saver sit-and-reach change scores (post-intervention – pre-intervention), followed by the Bonferroni adjustment, showed that the students that performed the stretching program during the cold-down period significantly improved their hamstring extensibility levels compared to the control group (p < 0.001). However, statistically significant differences between the warm-up/ both periods groups and the control group were not found (p > 0.05). Conclusions. In order to develop students’ flexibility, PE teachers should apply stretching programs during the cold-down period. Due to the negative effect of static stretching on performance as previously found in the literature, it seems that PE teachers should improve students´ flexibility during the cool-down period of the sessions.
Keywords: Educación física; PE-based planning; Flexibility; Back-saver sit-and-reach test; Primary education